A single phase SEPIC AC-DC converter with improved power factor and input current THD - Hossain, Mohammad Rubaiyat Tanvir; Abedin, Amina Hasan; Choudhury, Mohammad Ali A.Shoukat (© 2016 IEEE, 2018)
This conference paper was published in the International Conference on Electrical and Computer Engineering, ICECE 2016; ECE Building, Bangladesh University of Engineering and TechnologyDhaka; Bangladesh; 20 December 2016 through 22 December 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICECE.2016.7853934 The Journal's website is at: https://ieeexplore.ieee.org/document/7853934/